Marxismo y Dependencia. / Marxism and dependence. - SOTELO VALENCIA, Adrián (Utopía y Praxis Latinoamericana, 2020)
RESUMEN El artículo sostiene que para entender la teoría de la dependencia en la vertiente que desarrolló el pensador brasileño Ruy Mauro Marini en su Dialéctica de la dependencia y en otros textos, sólo puede entenderse en el contexto conceptual, categorial, metodológico y analítico de la crítica de la economía política y del marxismo, en particular con los insumos de El capital y los Grundrisse de Marx, y los desarrollos programáticos de Lenin con sus teorías del Estado y del imperialismo. ABSTRACT The article maintains that in order to understand the theory of dependence in the slope developed by the Brazilian thinker Ruy Mauro Marini in his Dialectic of Dependence and in other texts, it can only be understood in the conceptual, categorical, methodological and analytical context of the critique of political economy and Marxism, in particular with the inputs of Capital and Marx’s Grundrisse, and Lenin’s programmatic developments with his theories of the State and imperialism.